Studies On The Formulation And Mechanical And Dynamic Properties Of Natural Rubberichloroprene Rubber Blend For Rubber Bushing Application - Sethu, Puspalatha (2006)

(untitled)
Suatu kajian sistematik, berasaskan formulasi-formulasi adunan getah asli dan getah kloroprena (NRlCR), telah dijalankan llntuk mendapatkan satu formulasi yang sesuai untuk bush getah. Kedua-dua sifat-sifat statik dan dinamik telah diarnbilkira. Sifat-sifat penting yang diambilkira untuk aplikasi bush getah ialah set mampatan yang baik, rintangan penuaan yang baik, dan pernencilan getaran yang baik dengan transrnisibiliti yang rendah. Sebatian permulaan yang digu,nakan adalah satu forrnulasi 100% getah asli biasa yang digunakan untuk galas getaran. A systematic investigation, based on natural rubber and chloroprene rubber (NRlCR) blend formulations, were carried out to develop a suitable formulation for rubber bushing. Both static properties and dynamic properties were considered. The important properties considered for rubber bushing application were good compression set, good ageing resistance and good vibration isolation with low transmissibility. The starting and reference compound used is a typical 100% NR formulation used for vibration mounting.